Deteksi Bakteri Salmonella sp. dengan Kultur Darah Pada Pasien Widal Positif di Laboratorium Klinik X - Nurul Istiqomah; Novia Agustina; Salsa Bellamilenia Putri (Journal Syifa Sciences and Clinical Research, 2023)
Until now, the gold standard test for diagnosing typhoid fever is a bacterial culture or also known as a gall culture examination. Blood cultures have the best sensitivity (40–60%) when performed in the first-early second week. Purpose: this study aims to identify the presence of Salmonella sp. in the blood of Widal positive patients. Method: this research is a descriptive study with a cross-sectional approach. This study used the blood culture method. The media used in this study were oxgall, SSA, KIA and IMViC media. The results showed that 20% of Salmonella typhi bacteria were found, 7% of other bacteria and 73% of bacteria did not grow on the media. The macroscopic characteristics of salmonella bacteria found were round colonies, clear in color, convex surface, flat colony edges, semi mucoid consistency, no reduction of tellurit. The microscopic characteristics are rod-shaped, spread arrangement, red in color and are Gram negative. Cultivation on IMViC media showed Indole -, MR +, VP -, Citrate -, KIA medium alkaline slope, acid base, H2S +, gas -. Conclusion: Salmonella thypi was found in the blood cultures of positive widal patients.